Quality of life outcomes of adenotonsillectomy for obstructive sleep disorders: our experience in a Tertiary Care Centre in Ghana - Kitcher, E.D.; Searyoh, K.; Abaidoo, B. (West African journal of medicine, 2013)
RESULTS: Thirty-one children with a mean age of 5.08 ± 0.95 years were seen. The mean OSA-18 preoperative score for Study1 was 4.27 ± 0.27; the mean OSA 18 post operative scores for Study1 and Study 2 were 1.93 ± 0.25 and 1.78 ±0.31 respectively. There was a significant reduction in the mean post operative OSA 18 score for both studies compared to the corresponding preoperative mean score (p-value = 0.001). The mean postoperative overall quality of life scoresfor Study 1 and Study2 were 8.52 ± 0.53 and 7.68 ± 1.06 respectively.CONCLUSION: There was significant improvement in long term quality of life outcomes following adenotonsillectomy for OSDs.METHODS: The subjects for this study were cohort of children who were part of a study named Study1 carried out at E.N.T. Unit, Korle Bu Teaching Hospital, Accra. These children had adenotonsillectomy for OSDs and their quality of life were evaluated preoperatively and again four to six weeks post operatively using Obstructive Sleep Apnoea 18 (OSA 18 ) questionnaire; a quality of life assessment tool. Thirty five children who were at least nine months post adenotonsillectomy were invited to a follow up E.N.T.clinic for the current study named Study 2 and their quality of life were again evaluated using OSA 18 questionnaire.BACKGROUND AND OBJECTIVES: Obstructive Sleep Disorders (OSDs) impacts negatively on the quality of life of children. However the long term outcomes of adenoton-sillectomy remain unknown. The aims and objectives of this study was to assess the long term quality of life of Ghanaian children withRESULTS: Thirty-one children with a mean age of 5.08 ± 0.95 years were seen. The mean OSA-18 preoperative score for Study1 was 4.27 ± 0.27; the mean OSA 18 post operative scores for Study1 and Study 2 were 1.93 ± 0.25 and 1.78 ±0.31 respectively. There was a significant reduction in the mean post operative OSA 18 score for both studies compared to the corresponding preoperative mean score (p-value = 0.001). The mean postoperative overall quality of life scoresfor Study 1 and Study2 were 8.52 ± 0.53 and 7.68 ± 1.06 respectively.CONCLUSION: There was significant improvement in long term quality of life outcomes following adenotonsillectomy for OSDs.METHODS: The subjects for this study were cohort of children who were part of a study named Study1 carried out at E.N.T. Unit, Korle Bu Teaching Hospital, Accra. These children had adenotonsillectomy for OSDs and their quality of life were evaluated preoperatively and again four to six weeks post operatively using Obstructive Sleep Apnoea 18 (OSA 18 ) questionnaire; a quality of life assessment tool. Thirty five children who were at least nine months post adenotonsillectomy were invited to a follow up E.N.T.clinic for the current study named Study 2 and their quality of life were again evaluated using OSA 18 questionnaire.BACKGROUND AND OBJECTIVES: Obstructive Sleep Disorders (OSDs) impacts negatively on the quality of life of children. However the long term outcomes of adenoton-sillectomy remain unknown. The aims and objectives of this study was to assess the long term quality of life of Ghanaian children with OSDs undergoing adenotonsillectomy.
Keywords: Quality of life; adenotonsillectomy; sleep disorders; Ghana; OSDs